Central fixation detection with an open-frame retinal birefringence scanning system: Optics, optomechanics, polarization balancing aspects, computer modeling and simulation - Gramatikov, Boris I.; Irsch, Kristina; Guyton, David L. (Optics and laser technology, 2023)
•Retinal imaging systems rarely incorporate technology for foveal tracking.•Retinal Birefringence Scanning (RBS) allows fast detection of central fixation.•RBS can be used conjointly with any imaging technology and guide it.•RBS is polarization sensitive and not trivial to integrate with.•Mueller-matrix-based computer model may optimize polarization-sensitive systems. There is a growing need to add a fast fixation-detection system or even an eye-tracking system to various diagnostic and some therapeutic ophthalmic technologies. For example, this would enable registration of stable images of the fovea. In recent years we have developed rapid technologies that detect the location of the fovea using retinal birefringence scanning (RBS). Yet, combining it with ophthalmic imaging technologies is not trivial, mainly because RBS employs polarized light and polarization-sensitive optics, while most ophthalmic imaging systems do not. Therefore, integrating these two types of systems optically poses a significant challenge, especially to the RBS system. Using principles from polarization optics and Mueller-matrix-based computer modeling for optimization, we developed a prototype of an open-frame RBS system as a potential adjunct fixation monitoring technology, with a promise to reduce the interference created by eye movements in advanced ophthalmic imaging technologies, such as optical coherence tomography, fluorescein angiography, scanning laser ophthalmoscopy, and others. Our technology is fast, does not need calibration, and uses true anatomical information from the retina for fixation detection. It enables adding fixation monitoring capabilities without having to modify the main imaging system, and has the potential to facilitate imaging without anesthesia in otherwise challenging subjects and/or patients, such as young children.